Sistem Informasi Pendataan Keluarga Miskin Dengan Parameter Penghasilan Dan Kondisi Rumah Berbasis Web - Fajri Utama; Surmayanti (Journal of Computer Scine and Information Technology, 2024)
Efficient, Accurate And Safe Data Collection Is Needed For The Administration Of An Agency. This Information System for Data Collection for Poor Families Supports the Work of Employees to Perform Data Collection in an Efficient, Accurate, and Safe manner. And to help determine the objectivity of poor families. In accordance with the objectives of making an information system, this activity is carried out using research methods in the form of observation, documentary media, and library research. The Solok Ambah Nagari Office in carrying out data collection still uses manual data collection by recording on a piece of paper. And as technology develops, an information system for collecting data on poor families is created, intended to make it easier for employees to manage data and expand information to the public and related parties. In this information system, there are two users, namely Admin and Kaur. In the Information System for Data Collection for Poor Families, the Program is Made Using Php and MySQL as the Database. The resulting poor family data collection information system is equipped with a poor family report search facility. And this system can help Nagari Solok Ambah officers store population data, determine poor families